0312 Creating A Standardized Procedure for Sleep Measured by Actigraphy in Aviation Field Studies. (12th April 2019) - Lamp, Amanda; Rasmussen, Ian; Cook, Maxwell; Smith, Rhiannon Soriano; Gage, Natasha; Belenky, Gregory
Abstract: Introduction: The Actigraph is a wrist-worn device containing an accelerometer that can detect changes in activity to measure sleep within individuals and quantify sleep across populations. While there is some literature comparing actigraphy with other sleep scoring methods, the exact nature of data-cleaning procedures for actigraphy is not well defined, and varies from laboratory to laboratory. There is a need for a standardized data-cleaning procedure. We have developed such a procedure to showcase its use when monitoring the sleep of commercial aviation pilots. Methods: Our standardized actigraphy data cleaning procedure is a two-step process. The first step is to identify by self-report, event markers, and activity level, periods of time that are highly likely to be wake in the actigraph report. The second step is to take the remainder of the report and determine which, by the same criteria, periods of time that are possibly sleep are in fact sleep. This method was compared to auto-generated sleep only and self-report only (applied to data collected from pilots) to demonstrate that our procedure more accurately measures actual sleep. Results: We have found the two-step procedure renders a more accurate and reproducible sleep/wake history, compensating for mistakes made by pilots when self-reporting sleep and eliminating most inaccuracies made when only actigraph sleep algorithms are used. Conclusion: In light of what our data shows, and the overall lack of literature surrounding actigraphy cleaning procedures, we highly recommend a standardized data cleaning procedure. While we apply the cleaning procedure to pilot's sleep data and believe it should be implemented for all aviation studies, this procedure may also be useful across multiple population types. Support (If Any): United Airlines